Occurrence of proventriculo-ventricular intussusception in chicken - A one-year perspective study - M. Pradeep; M.R. Reddy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Proventriculo-ventricular intussusception is the telescoping of proventricular portion of the avian stomach into the ventriculus. Even though occurrence of intestinal intussusceptions in chickens commonly observed, the reports on proventriculo-ventricular intussusceptions were very scarce. The study was done as a part of screening the gut lesions in the chicken carcasses for a period of one year and 18078 chicken carcasses of multiple age groups belonging to 15 pure line breeds and two commercial breeds were screened. Proventriculoventricular intussusceptions noticed in two female PD2/Vanaraja chicks of 4 days and 3 weeks of age and in a 9 weeks old male Nicobari grower. While the intussuscepted proventriculus of Vanraraja chicks had unremarkable inflammatory lesions, severe congestion of proventriculus along with koilin displacement in the anterior portions of ventriculus were evident in Nicobari grower. The present study, point out the occurrence of proventriculoventricular intussusception in young synthetic and native lines of chicken.